2008
DOI: 10.1099/vir.0.2008/001412-0
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and host range studies of Maruca vitrata nucleopolyhedrovirus

Abstract: The complete genome of the Maruca vitrata nucleopolyhedrovirus (MaviNPV) isolated from the legume pod borer, Maruca vitrata (Lepidoptera: Pyralidae), was sequenced. It was found to be 111 953 bp in length, with an overall 39 % G+C content, and contained 126 open reading frames (ORFs) encoding predicted proteins of over 50 aa. The gene content and gene order of MaviNPV have the highest similarity to those of Autographa californica multiple nucleopolyhedrovirus (AcMNPV) and their shared homologous genes are 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 94 publications
0
26
0
Order By: Relevance
“…It also had an identity of 88% with folding protein or F protein of PxMNPV (Harrison and Lynn, 2007), and with a folding protein of A. californica as well (Ayres et al, 1994). However, an identity of 84% was observed with a fusion protein of RoMNPV (Harrison and Bonning, 2003), whereas a 65% identity to MvMNPV was detected (Chen et al, 2008).…”
Section: Bmmnpv Orf10 and Orf14 Amino Acid Sequencesmentioning
confidence: 88%
See 1 more Smart Citation
“…It also had an identity of 88% with folding protein or F protein of PxMNPV (Harrison and Lynn, 2007), and with a folding protein of A. californica as well (Ayres et al, 1994). However, an identity of 84% was observed with a fusion protein of RoMNPV (Harrison and Bonning, 2003), whereas a 65% identity to MvMNPV was detected (Chen et al, 2008).…”
Section: Bmmnpv Orf10 and Orf14 Amino Acid Sequencesmentioning
confidence: 88%
“…The analysis of ORF14 nucleotide sequence revealed that the sequence of MNPV subgroup of B. mori (BmMNPV) had identity equivalent to 99, 94, 93, 89, 79%, respectively, with: BmNPV genome, isolate T3 (Gomi et al, 1999); AcMNPV genome, clone C6 (Ayres et al, 1994); PxMNPV genome, isolate CL3 (Harrison and Lynn, 2007); RoMNPV genome (Harrison and Bonning, 2003), and MvMNPV genome (Chen et al, 2008). …”
Section: Orf14 Sequence Analysismentioning
confidence: 99%
“…The recently completed genome sequence of Maruca vitrata NPV (MaviNPV) lacks vfgf (Chen et al 2008). Assays of AcMNPV and BmNPV vFGF protein function show properties consistent with those of a growth factor.…”
Section: Baculovirus Genes That Enhance Infectionmentioning
confidence: 99%
“…Among these genes, alk-exo was conserved in all baculovirus and fgf and was conserved in all lepidopteran baculoviruses [20]. Actin rearrangement-inducing factor-1 (arif-1) and ptp-1 was another two auxiliary genes, but absent in EupsNPV [26]. Homologous repeat sequences (hrs)…”
Section: Auxiliary Genesmentioning
confidence: 99%